Un établissement rural gallo-romain à Gellainville " Le Radray " (Eure-et-Loir) (fin du Ier s. av. J.-C.-fin du IVe s. ap. J.-C.) - Hervé Delhoofs; Julie Rivière; Jonathan Simon; David Wavelet (Revue Archéologique du Centre de la France)
Abstract: The site of "Radray" in the municipality of Gellainville (28) has been excavated in 2007. The article presents the main results of the Gallo-Roman part of the site. The occupation begins from the first half of the first century A.D. During the augustean period, a "parcellaire" system gets organized and the first buildings are established. Since the middle of the first century, the space is organized for the setting up of a rural settlement. On both sides of a rural path, the farming is distribued in two groups: eastwards the residential part and the outbuildings, westwards the agricultural part and the farming buildings. The settlement is abandoned during the third century. The structures of the late antiquity do not follow the former limits. The occupation is materialized by four pouds and some buildings disposed inside und south of a trapezoïdal enclosure. Besides a little group of aerial storehouses is settled apart, towards the south west. The systematic surrender of the habitation structures from 375 A.D. Shows a global transformation of the area.